Interactions between attained proficiency and length of exposure to lexical attrition of English as a second language - Li, Hui Helen; Feng, Ying; Bao, Changhui; Bai, Yanyuan (Frontiers in Psychology, 2025)
Compared to the considerable scholarly focus on language acquisition, research into language attrition has not received as much attention. Current studies have tended to emphasize either linguistic or extralinguistic factors impacting language attrition, rather than examining how these various factors might interact with one another. Consequently, it remains unclear whether there are any interactional effects among the different contributing elements of language attrition. This paper explored the relationships between attained proficiency and duration of exposure through a vocabulary assessment conducted with going-to-be sophomores (n = 110). The findings indicated that the attained proficiency served as an initial factor, while the lengths of exposure to a foreign language reflected the extent of language attrition. Additionally, different types of exposure were also found to be influential for lexical attrition. These results provide valuable insights for second language pedagogy and help enhance students’ capabilities in acquiring foreign languages.